Understanding Community Insecurity in Nigeria: A Multifaceted Approach - Oluwalogbon, Leke Abraham (Kashere Journal of Politics and International Relations, 2024)
The unprecedented spread of insecurity in the West African region is alarming and mind-bugging to the citizens and local and international communities. The spate of community insecurity cuts across Mali, Cameroon, Chad, Niger and Nigeria, with its manifestation in insurgency and terrorism, secessionist movements, religious conflicts, urban crimes, ethnic violence, banditry, abduction, mass killings, suicide bombing, rape, disruption of properties, herders and anti-democratic activities. However, the phenomenon has become more evident in Nigeria in the last fifteen years as new dimensions of insecurity with more devastating implications are emerging. The core of human, economic, and political security is prevention-oriented responses to community-based crises by the government and individuals within the environment. The absence of community insecurity is human safety, economic empowerment, and democratic advancement. Its existence, however, poses human, financial, and political security questions among scholars and policy-makers alike in the global environment. The attempt to solve the questions has culminated in adopting different security strategies ranging from self-help security arrangements and community policing at the local level to joint security task forces at state and central levels in Nigeria. The complexity of issues like social inequality, marginalisation, weak institutions, human rights abuse, bad governance, poverty, globalisation, militarization of migrants, constitutional abuse, and widespread corruption are very germane to the contextualisation of community insecurity. Contingency model has been employed to explain the causation and control of community insecurity.